MARKED PERSONAL NAMES: AN ANTROPONIMIC STUDY OF BALINESE STUDENTS’ NAMES IN DENPASAR - Iwan Indrawan, Ni Made (e-Journal of Linguistics, 2012)
The research aims to account for the Marked Balinese Students’ Personal Names. Four research problems are studied, namely (1) the criteria used to distinguish the marked names (NDMBmk) and the unmarked ones (NDMTBmk), (2) the functions of the markedness, (3) the factors that influence it, and (4) the ideologies that operate behind it. The markedness of personal names reflect a relation between the arbitrariness in language uses and the extralinguistic factors influencing it. In the context of Balinese, the tradition, legal practices, and the globalisation may affect the arbitrariness. In order to determine NDMBmk, criteria of markedness was constructed. According to the criteria, structurally, NDMBmk consist of at least five elements, as Anak Agung Arim Kasunu Arya Penarungan . Behaviorally, they may consist of names not derived from Balinese and/or Sanskrit, such as Giovani on I Gede Adeyaka Giovani , adopt a foreign spelling system as Chrisna on Ni Putu Chrisna Wulandari , or use no markers of Balinese ethnics or caste as Yunisari Wira Putri . Out of 698 sampled names, NDMBmk are found 54. Besides denoting, the marked elements also function to distinguish personal identities, to shape the existence of the name holder, to connote particular perception, and to reflect the changing era. The factors influencing the markedness are the need to express something new, a wish to acculturate, to raise status or keep a distance socially, and to demonstrate a linguistic expertise, or when seeing from the concept of imagery, the factors are the imagery on something new and on social status or distancing. The ideologies behind the phenomenon are globalist, nationalist, and the casteless-Balinese.
Keywords: markedness, criteria, personal names, Balinese, function, factor, ideology